Fast Synthesis of Complex Enantiopure Heterocyclic Scaffolds by a Tandem Sequence of Simple Transformations on α‐Hydroxyaldehydes. Issue 28 (10th June 2013) - Cannillo, Alexandre; Norsikian, Stéphanie; Retailleau, Pascal; Dau, Marie‐Elise Tran Huu; Iorga, Bogdan I.; Beau, Jean‐Marie
Abstract : Two tandems are faster than one! Properly sequenced reactions initiated by the Petasis aminoalcohol synthesis from boronic acids, diallylamine, and α‐hydroxyaldehydes, including free aldoses, leads to rapid construction of complex enantiopure structures (see scheme).